Hubungan Tingkat Pengetahuan, Sikap Dan Kesejahteraan Psikologis Terhadap Pencegahan Stunting Pada Ibu Dengan Balita Di Desa Rancalabuh - Nurul Ijah; Lastri Mei Winarni; Ida Faridah (Gayaku Publisher, 2026)
Background: Stunting is a condition of growth disorder due to chronic malnutrition that remains a serious concern in Indonesia, including in Rancalabuh Village, where 23 out of 314 toddlers are experiencing malnutrition. This is largely caused by unhealthy eating patterns and a lack of maternal knowledge. Objective: his study aims to analyze the relationship between mothers' knowledge level, attitude, and psychological well-being towards stunting prevention efforts in toddlers in Rancalabuh Village, as well as to identify the most influential demographic factors. Methodology: This research employs a quantitative method with a descriptive correlational design and a cross-sectional approach, involving 176 mothers of toddlers in Rancalabuh Village selected using stratified random sampling. Data were collected using questionnaires and analyzed with Chi-Square tests (bivariate) and multiple linear regression (multivariate). Results: In this study, most mothers had high knowledge (90.9%), positive attitudes (94.9%), and high psychological well-being (85.5%). There was a significant relationship between knowledge (p=0.000), attitude (p=0.002), and mothers’ psychological well-being with stunting prevention, both partially and simultaneously. The mother’s occupation did not show a significant relationship with stunting prevention (p=0.019), while age and education did not. Conclusion: Mothers' knowledge level, and psychological well-being are significantly related to stunting prevention. Maternal occupation is the most influential demographic factor